Leveraging cloud computing for improved health service delivery: Findings from public health facilities in Kisumu County, Western Kenya‐2019. Issue 1 (18th May 2021) - Ogwel, Billy; Odhiambo‐Otieno, George; Otieno, Gabriel; Abila, James; Omore, Richard
Abstract: Introduction: Healthcare delivery systems across the world have been shown to fall short of the ideals of being cost‐effective and meeting pre‐established standards of quality but the problem is more pronounced in Africa. Cloud computing emerges as a platform healthcare institutions could leverage to address these shortfalls. The aim of this study was to establish the extent of cloud computing adoption and its influence on health service delivery by public health facilities in Kisumu County. Methods: The study employed a cross‐sectional study design in one‐time data collection among facility in‐charges and health records officers from 57 public health facilities. The target population was 114 healthcare personnel and the sample size (n = 88) was computed using Yamane formula and drawn using stratified random sampling. Poisson regression was used to determine the influence of cloud computing adoption on the number of realized benefits to health service delivery. Results: Among 80 respondents, Cloud computing had been adopted by 42 (53%) while Software‐as‐a‐Service, Platform‐as‐a‐Service and Infrastructure‐as‐a‐Service implementations were at 100%, 0% and 5% among adopters, respectively. Overall, those who had adopted cloud computing realized a significantly higher number of benefits to health service delivery compared to those who had not (Incident‐rate ratio (IRR) =1.93, 95% confidence interval (95% CI) [1.36‐2.72]). A significantly higher number of benefits was realized by those who had implemented Infrastructure‐as‐a‐Service alongside Software‐as‐a‐Service (IRR = 2.22, 95% CI [1.15‐4.29]) and those who had implemented Software‐as‐a‐Service only (IRR = 1.89, 95% CI [1.33‐2.70]) compared to non‐adopters. We observed similar results in the stratified analysis looking at economic, operational, and functional benefits to health service delivery. Conclusion: Cloud computing resulted in improved health service delivery with these benefits still being realized irrespective of the service implementation model deployed. The findings buttress the need for healthcare institutions to adopt cloud computing and integrate it in their operations in order to improve health service delivery.